Controllable growth of organic nanostructures from 0D to 1D with different optical properties. Issue 122 (24th November 2015) - Luo, Yusen; Xue, Zheng; Li, Yongjun; Liu, Huibiao; Yang, Wensheng; Li, Yuliang
Abstract : Controllable nano/microstructures from 0D to 1D were fabricated by adjusting the growth rate. The difference in symmetry between two molecules results in distinct self-assembly behaviours and different optical properties. Abstract : Two donor–π–donor (D–π–D) type compounds containing carbazole as electron donors around the perylene core were synthesized and fabricated into controllable nano/microstructures from 0D to 1D by adjusting the growth rate. The difference in symmetry between the two molecules results in distinct self-assembly behaviours. Fluorescence microscopy images and fluorescence spectra of these self-assembled structures displayed different optical properties. It is indicated that the photophysical properties of these two compounds in the solid state are determined not only by their chemical structures but also by the mode of molecular packing.